PELATIHAN PENINGKATAN SUMBER DAYA MANUSIA DI ERA REVOLUSI INDUSTRI 4.0 MENUJU MASYARAKAT 5.0 - Bramanto, Kristian Aldion (JURNAL DARMA AGUNG, 2024)
The industrial revolution that ushered in the new era of the industrial revolution 4.0 is a process that continuously changes the stages of automation in life that relies on the internet network system. Meanwhile, society 5.0 is a society that is able to answer various challenges and social problems by utilizing various innovations developed during the industrial revolution 4.0. This research uses qualitative research (library research), in data analysis the author uses descriptive analysis methods. The author uses literature and documentation techniques, the data analysis technique uses Lasswell's content analysis model. The fundamental understanding of human resource managers is that human resources (HR) who have low qualifications will lose their jobs, because the impact of the industrial revolution 4.0 will require human resources to have higher skills. The industrial revolution 4.0 both industry 4.0 and Society 5.0 emphasizes readiness to develop creativity and critical thinking, this is in line with the goals of the world of work in Indonesia. Based on this, the author concludes that it is necessary and important for the community to be ready to welcome and implement education for the Industrial Revolution 4.0 and Society 5.0.